1965
DOI: 10.1002/jhet.5570020312
|View full text |Cite
|
Sign up to set email alerts
|

Morphanthridines II. 11‐aminoalkyl‐5,6‐dihydromorphanthridines

Abstract: Butyl lithium converts 5‐substituted‐5,6‐dihydromorphanthridines to the 11‐position anion. Treatment of this lithium anion with aminoalkyl halides affords the 11‐aminoalkylated derivatives. Catalytic hydrogenation causes reductive cleavage of benzylamino bridge of the morphanthridine ring, a reaction which is used to structurally relate these compounds to the known 11‐aminoalkylidene‐5, 6‐dihydromorphanthridines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
1984
1984

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…5,6-Dihydro-l1 -hydroxy-5-methyl-6-oxomorphanthridine. Sodium borohydride (4 g) was added in portions to a stirred, cooled suspension of 5,6-dihydro-5-methyl-6,11dioxomorphanthridine (Drukker & Judd, 1965) (10 g) in methanol (200 ml), the temperature being kept below 10". The mixture was stirred for 1 h at 10-15", diluted with water (150 ml), acidified with dilute hydrochloric acid and filtered.…”
Section: Methods Dmentioning
confidence: 99%
“…5,6-Dihydro-l1 -hydroxy-5-methyl-6-oxomorphanthridine. Sodium borohydride (4 g) was added in portions to a stirred, cooled suspension of 5,6-dihydro-5-methyl-6,11dioxomorphanthridine (Drukker & Judd, 1965) (10 g) in methanol (200 ml), the temperature being kept below 10". The mixture was stirred for 1 h at 10-15", diluted with water (150 ml), acidified with dilute hydrochloric acid and filtered.…”
Section: Methods Dmentioning
confidence: 99%
“…The anion was generated with sodamide in refluxing toluene (16). We have found that the sodium salt is more conveniently generated with sodium hydride in dimethyl formamide at room temperature.…”
Section: -Methyl-56-diliydro-11mentioning
confidence: 99%
“…
Because of our interest in the preparation of basic substituted morphanthridines (1,2 ) , we have investigated the Bischler-Napieralski cyclization of 2-acylaminobenzophenones in an effort to obtain the useful intermediates, 11morphanthridones. This cyclization method was applied quite successfully for the preparation o€ 6substituted morphanthridines from 2acylaminodiphenylmethanes (3,4), a s well a s for the synthesis of related oxazepines and thiazepines (4, 5).However, when we treated 2formylamino-5chlorobenzophenone (la) with hot polyphosphoric acid, only 2 -amino -5chlorobenzophenone was isolated.
…”
mentioning
confidence: 99%